Analisis Rasio Likuiditas dan Rasio Solvabilitas dalam Menilai Kinerja Keuangan pada PT Akasha Wira International Tbk Periode 2021-2024 - Sarti Enne; Rindiantika Rindiantika; Nia Bonggakarua; Muhammad Haekal Yunus; Rafiqah Asaff (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the financial performance of PT Akasha Wira International Tbk during the 2021–2024 period through a liquidity ratio and solvency ratio approach. The liquidity ratio used includes the current ratio, quick ratio, and cash ratio, while the solvency ratio includes the debt to asset ratio (DAR) and debt to equity ratio (DER). The research method used is quantitative descriptive using secondary data in the form of the company's annual financial statements obtained from the official website of the Indonesia Stock Exchange and other relevant supporting sources. The results show that the company's current ratio, quick ratio, and cash ratio are consistently above industry standards, which indicates that the company has excellent ability to meet its short-term obligations. This shows that the company has strong liquidity and is able to maintain its operational stability without facing financial difficulties in the short term, even in volatile economic conditions. Meanwhile, the results of the solvency ratio analysis show a downward trend in the value of DAR and DER from year to year, which reflects that the company's capital structure is getting healthier and dependence on debt is decreasing. This decline is a positive indication that the company is starting to rely on its own capital to support its operational and investment activities in a sustainable manner. Overall, the results of this study conclude that PT Akasha Wira International Tbk's financial performance during the 2021–2024 period is in a "healthy" condition both in terms of liquidity and solvency. These findings can be used as a reference for investors, management, academics, and other interested parties in assessing the company's financial stability and future prospects.